2022
DOI: 10.32604/jrm.2022.017759
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Eco-Friendly Composites Made from Wood Dust and Recycled Polystyrene

Abstract: The development of alternative wood composites based on the use of waste or recycled materials can be beneficial due to over exploitation of natural resources. Under this frame, an option for the successful utilization of waste polystyrene which avoids environmental problems that formaldehyde adhesives cause and also reduces waste disposal, is its potential application as a binder for the production of value-added environmentally friendly and low cost wood composites. Two types of panel were successfully made,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
1
0
2
Order By: Relevance
“…In composite research, binder is one of the components usually utilized as an adhesive to bind fiber particles together and form a dense fiber network in composite panels. 20 Typically, the binder retains the fiber by serving as a load carrier and smoothly absorbing the created stress in the composite panel. 21 Several studies have shown that the physical and mechanical properties of a composite panel have greatly improved when there is more interaction occurred between the binder and the fiber particles.…”
Section: Composite Panelmentioning
confidence: 99%
“…In composite research, binder is one of the components usually utilized as an adhesive to bind fiber particles together and form a dense fiber network in composite panels. 20 Typically, the binder retains the fiber by serving as a load carrier and smoothly absorbing the created stress in the composite panel. 21 Several studies have shown that the physical and mechanical properties of a composite panel have greatly improved when there is more interaction occurred between the binder and the fiber particles.…”
Section: Composite Panelmentioning
confidence: 99%
“…Hypothetically, the successful use of waste polystyrene as a binder for the production of wood composites can help avoid the environmental and waste disposal issues bought about by the use of formaldehyde-based adhesives. Such an analysis was conducted in Foti et al [73], where two types of a panel comprised of 15% and 30% recycled PS were fabricated. The higher PS content (30%) led to an improvement in water absorption (165% and 750%, respectively, for recycled PS content of 15% and 30%) and thickness swelling.…”
Section: Sustainable Ps-based Materials Designmentioning
confidence: 99%
“…An interaction mechanism between the sawdust particles and the PS was developed (Figure 30). Overall, it was concluded that the wooden boards produced using waste PS as a binder could facilitate cleaner and more sustainable production [73]. The continued over-exploitation of non-renewable resources has made the development of alternatives, such as wood/recycled polymer composites, a highly beneficial research route.…”
Section: Sustainable Ps-based Materials Designmentioning
confidence: 99%
“…Fonte: Próprio autor(2022) Analisando a propriedade de densidade dos painéis presente na Tabela 3, é notório que os tratamentos não se diferenciam estatisticamente entre si, entretanto, utilizando como base a norma ANSIA.208.1 (2016), observa-se que os três tratamentos são considerados painéis de média densidade, em que os tratamentos 1 e 2 correspondem ao tipo M-S, enquanto o tratamento 3, ao tipo M-3. Por outro lado, utilizando a mesma norma, porém, mais antiga publicada em 1999, os tratamentos 1 e 2 poderiam ser caracterizados como painéis de baixa densidade do tipo LD-1, enquanto o tratamento 3 assumiria o lugar de painel de média densidade do tipo M-S.Ainda com relação aos dados presentes na Tabela 3, no entanto, observando as propriedades mecânicas, as quais são pré-estabelecidas pela norma ANSIA.208.1 (1999), todos os tratamentos atingiram os requisitos mínimos de acordo com seu tipo de painel correspondente, porém, quando comparados os resultados com a norma mais atual, ANSIA.208.1 (2016), nenhum tratamento atingiu os requisitos mínimos.…”
unclassified
“…Médias seguidas de letras iguais se diferem estatisticamente pelo teste de Tukey (p<0,05). **(coeficiente de variação).Fonte: Próprio autor(2022) Sruti et al (2021) produziram um biocompósito em formato de placa composto por pó de aguapé e cinzas de sabugo de milho com resina epóxi como adesivo nas proporções de 5, 10 e 15% em peso. Os autores concluíram que a placa com melhor resultado térmico foi a composta por 90% de pó de aguapé e 10% de cinzas de sabugo de milho, resultando em umacondutividade térmica de 0,305 W/m.K.…”
unclassified